2022
DOI: 10.1001/jamanetworkopen.2022.15227
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Medicare Advantage vs Traditional Medicare for Health Care Access, Affordability, and Use of Preventive Services Among Adults With Low Income

Abstract: Key Points Question How do health care access, preventive care use, and affordability of care compare between adults aged 65 years or older with low income enrolled in Medicare Advantage vs traditional Medicare? Findings In this cross-sectional study of 2622 adults with low income, no associations for most measures of health care access and preventive care use were observed between Medicare Advantage vs traditional Medicare. These adults were similarly like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…When Medicare Advantage was launched in 2003, agencies expected improved affordability and widened coverage as the program provided protection from extreme out-ofpocket expenses and added supplemental benefits. Previous studies on Medicare Advantage have demonstrated reduced expenses but have varied results regarding health quality, access, and outcomes [10,[12][13][14]16,17]. In our study, we noted a lack of improvement in utility and accessibility among Medicare Advantage plans for cancer survivors, which raises important questions about the value and cost-effectiveness of the extra benefits offered to beneficiaries.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…When Medicare Advantage was launched in 2003, agencies expected improved affordability and widened coverage as the program provided protection from extreme out-ofpocket expenses and added supplemental benefits. Previous studies on Medicare Advantage have demonstrated reduced expenses but have varied results regarding health quality, access, and outcomes [10,[12][13][14]16,17]. In our study, we noted a lack of improvement in utility and accessibility among Medicare Advantage plans for cancer survivors, which raises important questions about the value and cost-effectiveness of the extra benefits offered to beneficiaries.…”
Section: Discussionmentioning
confidence: 58%
“…Most Medicare Advantage plans are funded by risk-adjusted, fixed, per-person payments for beneficiaries, which creates an incentive to be cost effective when delivering care. While this incentive could lead to a larger emphasis on value-based and preventative care, it could also lead to the rationing of healthcare resources and possible avoidance of necessary care [10]. Further, Medicare Advantage plans can be a valuable tool for managing the high costs of cancer treatment, but may include more restrictions on the providers and services that are covered, and may require higher premiums than traditional Medicare does [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this study cannot reliably assess which hospitalizations were necessary vs potentially wasteful, nor which encounters were appropriately triaged to observation status or directly treated and discharged from the ED. Other work has found that Medicare Advantage is no different nor does it outperform traditional Medicare when focused on other elements of quality (eg, measures of ambulatory care) and narrow subpopulations. Yet the active use of ACSCs by policy makers to assess Medicare Advantage quality (eg, star ratings) creates incentives for plans to reduce ACSCs, thereby making it important to study these measures.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is ambiguous whether networks would reduce the number of unique PCPs seen by beneficiaries. Indeed, there is evidence MA‐PD beneficiaries may actually see more unique PCPs than those in PDPs 17 . Thus, for PCPs, the O/E ratio may be greater than 1 (Appendix A1).…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…Indeed, there is evidence MA-PD beneficiaries may actually see more unique PCPs than those in PDPs. 17 Thus, for PCPs, the O/E ratio may be greater than 1 (Appendix A1).…”
Section: Conceptual Frameworkmentioning
confidence: 99%